Identificación de escherichia coli y estafilococo aureus, en teléfonos celulares de estudiantes de quinto a décimo semestre de la clínica odontológica de la Universidad Antonio Nariño, sede Bucaramanga. (2020)
Introduction: Previous studies show cell phones used by health personnel carry bacteria considered pathogens that cause infection. There is no information on this in the clinical practices at University Antonio Nariño. Objective: To study the presence of Escherichia coli y Staphylococcus aureus in cells phones carry by dental students in their universitary clinical practices. Methods: A descriptive cross-sectional study was performed, sampling 60 cell screens using smears. The UFC count was performed on nutrient agar and culture on blood agar, MacConckey agar, citrate agar, catalase and novobiocin sensitivity tests for the identification of E. coli and S. aureus. The data was analyzed through the Excel 2013. Results: Microbial growth was obtained in 59 (98.33%) cell screens, a total of 90 microorganisms samples were isolated from which (57 Gram positive and 33 Gram negative). The total isolation corresponded to 50% S. epidermidis, 18% E. coli, 18% S. aureus, 10% S. saprophyticus and 3% yeast. For 58.3% of the samples, a total count of microorganisms greater than 10 cfu / ml was obtained. 67% of sampled cell phones are always handled during clinical practices and in 70% of cases with gloves in use. 3% of cell phones are never cleaned or disinfected. Conclusion: In the dental care environment, it is essential to control biosecurity, in order to avoid cross-contamination since cell phone screens act as fomites and can transmit potentially pathogenic microorganisms. Therefore, it is advisable to create protocols for disinfecting it and restricting its use in the most polluted areas of the clinic, in addition to encouraging students and teachers to frequent handwashing.